Historia sztuki - Robinson, Walter; Lubiak, Jaroslaw (Poznan : Dom Wydawniczy Rebis, 2000)
Polish translation of "Instant art history". A concise history of art from pre-historic times to the present.
Translation of: Instant art history.
Includes index.
Keywords: Art -- History